2020
DOI: 10.1017/qua.2020.86
|View full text |Cite
|
Sign up to set email alerts
|

Causes and implications of Mid- to Late Holocene relative sea-level change in the Gulf of Kachchh, western India

Abstract: The relict intertidal deposits from the Kharod River Estuary, Gulf of Kachchh, and the distal end of Kori Creek are used to infer the Mid- to Late Holocene relative sea-level (RSL) change in western India. Employing sedimentology, geochemistry, palynology, ichnology, and optical and radiocarbon dating, the study suggests the dominance of fluvial activity between 16.5 ± 1.6 and 9.9 ± 0.7 ka. After ~7 ka (7.3 ± 0.4, 6.8 ± 0.5 ka), the sea level showed a positive tendency until 4.7 ± 0.2 ka. The tectonically corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 128 publications
(209 reference statements)
0
10
0
Order By: Relevance
“…At places, the relict intertidal flats are preserved in the spit-sheltered location. Such sheltered locations with low tidal amplitudes and restricted wave activity have deposited fine, cohesive deposits in low energy environments (weakest current) occur at various elevations from the present-day tidal amplitude (Sharma et al 2020). Thakkar et al (1999Thakkar et al ( , 2001 reported the Quaternary sequences within the rocky mainland in the form of three major episodes as alluvial and colluvial fan deposits as Early Pleistocene, sandy sheets of miliolites with boulders and pebbles as middle Pleistocene and fluvial sand silt and clay with some aeolian deposits of late Pleistocene and Recent age.…”
Section: Stratigraphymentioning
confidence: 99%
“…At places, the relict intertidal flats are preserved in the spit-sheltered location. Such sheltered locations with low tidal amplitudes and restricted wave activity have deposited fine, cohesive deposits in low energy environments (weakest current) occur at various elevations from the present-day tidal amplitude (Sharma et al 2020). Thakkar et al (1999Thakkar et al ( , 2001 reported the Quaternary sequences within the rocky mainland in the form of three major episodes as alluvial and colluvial fan deposits as Early Pleistocene, sandy sheets of miliolites with boulders and pebbles as middle Pleistocene and fluvial sand silt and clay with some aeolian deposits of late Pleistocene and Recent age.…”
Section: Stratigraphymentioning
confidence: 99%
“…In places, relict intertidal flats are preserved in the spit-sheltered locations. Such locations have low tidal amplitudes and restricted wave activity and have deposited fine, cohesive deposits in a low energy environment but now occur at various elevations compared to the present-day tidal amplitude (Sharma et al 2020).…”
Section: Sea Level Climate and Geo-archaeologymentioning
confidence: 99%
“…Since then, the basin has recorded several episodes of transgression and regression, documenting the variety of palaeoenvironments. The most recent period of the geological history, that is, the Holocene period, has speculatively witnessed transgressive–regressive cycle in the western continental margin of India (Banerji, Pandey, Bhushan, & Juyal, 2015; Das, Prizomwala, Makwana, & Thakkar, 2017; Desai & Patel, 2008; Makwana, Prizomwala, Chauhan, Phartiyal, & Thakkar, 2019; Patel & Desai, 2009; Patel, Desai, & Bhatt, 2001; Sharma et al, 2021; Solanki, Prizomwala, Makwana, & Solanki, 2021; Tyagi et al, 2012). The spatio‐temporal evidences of these are sparsely documented, and for reconstructing a reliable relative sea level history, more data are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the Great Rann of Kachchh (GRK) has been investigated for its evolutionary history, stratigraphy, and shallow subsurface nature (Glennie & Evans, 1976; Khonde et al, 2011, 2017,b; Makwana et al, 2019; Maurya, Khonde, Das, Chowksey, & Chamyal, 2013; Merh, 2005; Ngangom, Thakkar, Bhushan, & Juyal, 2012; Sarkar et al, 2020; Sharma et al, 2021; Thakkar, Mamata, Thakkar, & Juyal, 2012; Tyagi et al, 2012). The Ranns are considered as depocentres of Holocene sedimentation and thus ideal sites for reconstructing palaeoenvironmental history (Maurya et al, 2013; Merh, 2005).…”
Section: Introductionmentioning
confidence: 99%